TATHBIQU NAMUDZAJ AL-TA’LIM AL-TA’AWUNI MAKE A MATCH FI TA’LIM AL-MUFRODAD: لترقية اتقان المفردات العربية MAKE A MATCH تطبيق النموذج التعليم التعاوني - Amirul Mukminin; Aisyatul Hanun; Ainirrahmah (Cordova Journal, 2024)
This study is entitled “Application of Make A Match cooperative learning Model to improve Arabic vocabulary mastery of students in class VA MIN 5 Jembrana academic year 2023/2024". This study departs from the lack of models used by teachers, because teachers only as a transmitter of information through a monotonous learning model while students only as listeners without being able to think. Low student learning activities have an impact on the mastery of students who are less than optimal. The formulation of the problem in this study is (1) How the application of the Make A Match model in improving the Arabic vocabulary of students in Class 5A MIN 5 Jembrana Kecamatan Negara Kabupaten Jembrana academic year 2023/2024 (2) whether the use of the Make a Match model can improve students ' Arabic vocabulary. This study aims (1) to determine the activities of teachers and students in the application of Make A Match model (2) to determine the mastery of students in the application of Make a Match model. This study is a class action research conducted in two cycles with test instruments, observation and documentation. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects of this study were students of class VA MIN 5 Jembrana academic year 2023/2024 which amounted to 30 students. The results of this study indicate that the use of the Make A Match learning model can improve students ' mastery of Arabic vocabulary for the 2023/2024 school year. Students ' mastery of Arabic vocabulary based on test scores increased by 13.3% from pre-cycle 43.3% (13 students) to 56.6% (17 students) in cycle I, then increased by 33.4% from cycle I 56, 6% (17 students) to 90.0% (27 students) in Cycle II. The conclusion of this study is the use of Make A Match learning model can improve the mastery of Arabic vocabulary VA class students MIN 5 Jembrana.